Desarrollo de una aplicación web y móvil para agendamiento de citas médicas en el Centro de Salud Chambo - Intriago Usca, Francisco Javier (2024)
This research implements a web application responsible for scheduling medical appointments at the Chambo Health Center, expediting the medical care process, and fulfilling the requirements established by the health institution. A quantitative approach was using, and data was collected during performance test carried out in a determined period. The SCRUM agile software development methodology was used to construct the application as a collaborative and adaptive work model. Robust technologies were used, such as the Angular framework in the frontend, Nest,js in the backend, and PostgreSQL as a database management system. Communication between client and server was achieved using an API (Application Programing Interface). These tools created a scalable, maintainable, and secure application. The application performance evaluation used the FURPS (Functionality, Usability, Performance, Reliability, and Support) quality model, considering efficiency, response time, and resource usage. The specific performance measurement was executed through the Apache JMeter benchmark, performing simulations with real-time requests. The test results showed high efficiency (100%), a response time of 4 ms, and a resource usage of 20%, thus guaranteeing the performance and quality of the software.